PERFORMANCE IMPROVEMENT OF YOGURT THROUGH THE VARIATION OF ROSELLE EXTRACT ADDITION AND FERMENTATION TIME - Ike Sitoresmi Mulyo Purbowati; Karseno Karseno; Ali Maksum; Ibrahim Aldaw Ibrahim (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Yogurt was a functional drink that was high in nutritional value but had a relatively short shelf life. Roselle extract had a high content of bioactive compounds, namely anthocyanin, polypHenol, and vitamin C. The integration of yogurt with roselle extract was expected to improve product performance both from the properties of health and sensory. This study aimed to determine the effect of roselle extract addition and fermentation time on the characteristics of roselle-based yogurt products. The research method used was an experimental method with a completely randomized design with Duncan's further test with treatments (1) the addition of rosella extract consisted of 3 levels, namely 0.5, 1.5, and 2.5 %. (2) Fermentation time: 8, 12, and 16 hours. The observed variables included chemical (pH, total titrated acid/TTA, anthocyanins), microbiology (lactic acid bacteria/LAB), and sensory. The fermentation time affects the pH value and TAT. The 12 hours of fermentation time gave pH and TTA values, respectively: 3.77 and 1.23%. The variation in the addition of roselle extract significantly affected the anthocyanin, TTA, and LAB values. The addition of the extract as much as 1.5% gave the anthocyanins, TTA, and LAB value respectively 0.871 mg/mL, 1.31%, 561.11x 107CFU/mL. The best treatment was yogurt with a roselle extract concentration of 1.5% and 20 hours of fermentation. This yogurt had characteristic as follows: pH 3.7, TAT 1.33%, anthocyanins 0.8751 mg/mL, LAB 560 x 107 CFU/mL, reddish-yellow (4), distinctive aroma (4), Sour taste (4), fine texture (4), and liking (4).